2024
DOI: 10.1038/s44321-024-00059-5
|View full text |Cite
|
Sign up to set email alerts
|

ImmunoPET imaging of Trop2 in patients with solid tumours

Wei Huang,
You Zhang,
Min Cao
et al.

Abstract: Accurately predicting and selecting patients who can benefit from targeted or immunotherapy is crucial for precision therapy. Trophoblast cell surface antigen 2 (Trop2) has been extensively investigated as a pan-cancer biomarker expressed in various tumours and plays a crucial role in tumorigenesis through multiple signalling pathways. Our laboratory successfully developed two 68Ga-labelled nanobody tracers that can rapidly and specifically target Trop2. Of the two tracers, [68Ga]Ga-NOTA-T4, demonstrated excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Preclinical studies involving tumor-bearing mouse models and beagle dogs revealed good pharmacokinetics and diagnostic potential of the tracer. Moreover, in a pilot clinical trial involving patients with solid tumors, 68 Ga-NOTA-T4 immuno-PET noninvasively and accurately visualized varying Trop2 expression in primary and metastatic tumors 96 .…”
Section: Trop2-targeted Imagingmentioning
confidence: 99%
“…Preclinical studies involving tumor-bearing mouse models and beagle dogs revealed good pharmacokinetics and diagnostic potential of the tracer. Moreover, in a pilot clinical trial involving patients with solid tumors, 68 Ga-NOTA-T4 immuno-PET noninvasively and accurately visualized varying Trop2 expression in primary and metastatic tumors 96 .…”
Section: Trop2-targeted Imagingmentioning
confidence: 99%